Study and documentation of the ancient city of Bosraand role Archaeologicalusing GIS - Eid, Safieh; Ali, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The Aim of the research is identify of the effects in the historical city of Bosra, which is one of the important archaeological sites in Syria. In addition, it is still Populated city.Where the ancient city of Bosra suffer from a lack of documentation of archaeological monuments and tourist lack of digital and interactive maps in spite of its historical significance as a center of tourist,the research try to documentation of archaeological sites in Bosra. and produce different maps showing big amount of information entered into the database. with a focus on 45 archaeological sites designated by the French mission by using GIS technology. Resulted from the search data bank represents all geographic digital data for the province raised the shield and everything related to the historical city of Bosra.